AB0058 A simple set of validation steps identifies and removes false positive measurements in a sandwich elisa caused by anti-animal protein antibodies in arthritis plasma. (23rd January 2014) - Kragstrup, T. W.; Andersen, T.; Deleuran, B.; Jensen, T. V.; Larsen, M. H.
Abstract : Background: In spite of the widespred use of sandwich ELISAs in arthritis research recommendations on how to eliminate unspecific interference by rheumatoid factor and anti-animal protein antibodies frequently found in arthritis plasma are lacking. Objectives: The objective of this study was to design a simple set of steps for validating and optimizing a sandwich ELISA before using it for measuring arthritis plasma. As an example of an immunoassay for arthritis research an anti-IL-24 sandwich ELISA system was prepared with a monoclonal mouse capture antibody and a polyclonal goat detection antibody. Methods: Plasma samples from patients with rheumatoid arthritis and spondyloarthritis were analyzed. A simple set of validation steps identified signals from samples in wells coated with isotype matched control antibody (false positive results) and lack of recovery after spiking samples (false negative results). ELAST ® (Perkin Elmer) amplification kit was used to amplify HRP signal before addition of substrate. Results: Interference was removed after preincubating the arthritis plasma samples with goat or bovine IgG (10 µg/ml – 100 µg/ml), suggesting that anti-animal protein antibodies found in the plasma of the arthritis patients caused the false results. Additional testing showed that an amplification step, using ELAST could increase the signal-to-noise ratio. Furthermore we show that repetitive freeze-thaw cycles of the samples, the anticoagulant used in the samples and the buffer used for the standard curve could affect the calculated concentration of the analyte. Conclusions: This study establishes an in-house sandwich ELISA system and validates it for measuring arthritis plasma with a simple set of validation and optimization steps removing the anti-animal antibodies cross binding of capture and detection antibodies. Any sandwich ELISA to be used in arthritis research could be validated an optimized by a similar setup. Disclosure of Interest: None Declared